Pengaruh Budaya Kerja dan Kepuasan Kerja terhadap Kinerja Pegawai PT Kereta Api Indonesia Divre III Palembang - Syafitri Adilah; Hamid Halin; Muhammad Kurniawan (Universitas Batanghari Jambi, 2023)
The purpose of this research is to examine how PT Kereta Api Indonesia Divre III Palembang's work culture and workers' levels of job satisfaction affect productivity. The research is quantitative, including techniques like multiple linear regression. A total of 133 participants were included in the analysis, which was conducted in SPSS version 24. Probability sampling's simplest form, known as